The Indonesian Government’s Efforts to Ensure Safety and Provide Protection for Indonesian Migrant Workers - Rusaila Nuralisa; Lenny Husna (Fakultas Syariah IAIN Langsa, 2026)
Ideally, the state should play an active role in ensuring the safety and comprehensive protection of Indonesian Migrant Workers as part of its constitutional responsibility and commitment to safeguarding human dignity. However, in reality, numerous cases of violence, exploitation, and work-related accidents continue to affect Indonesian Migrant Workers, indicating a persistent gap between legal norms and their practical implementation. This study aims to examine the efforts of the Indonesian government in guaranteeing safety and providing legal protection for Indonesian Migrant Workers within the framework of national law. The research employs a library-based study with a qualitative approach, utilizing normative juridical analysis of statutory regulations and relevant scholarly literature. The findings reveal that Indonesia has established a relatively comprehensive legal framework, particularly through Law Number 18 of 2017, which positions the state as the primary duty bearer in the protection of migrant workers. Nevertheless, the effectiveness of such protection remains constrained by structural challenges, including weak law enforcement, fragmented institutional coordination, and limited policy implementation capacity. Therefore, strengthening the state’s role through consistent, integrated, and human-centred governance is essential to ensure the safety and protection of Indonesian Migrant Workers in the context of global labour migration.